Pengaruh Komunikasi Interpersonal Antarpegawai Terhadap Kinerja Pegawai Di Bagian Humas Kantor Bupati Maluku Tengah - Tuhuteru, Windasari; Muhiddin, Amir; Tahir, Nurbiah (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2021)
The purpose of this study was to determine whether there was an Influence of Interpersonal Communication Between Employees on Employee Performance in the Public Relations Section of the Central Maluku Regent's Office. The population in this study were all employees in the Public Relations Office of the Central Maluku Regent, amounting to 25 people. The sampling method used  saturated sample that used the entire population as a source of data. The data collection method used  a questionnaire. The analysis technique used simple linear regression, correlation analysis and t hypothesis test with the help of SPSS 16.0 software for windows. The results of this study showed that there was a significant influence between interpersonal communication on improving employee performance in the Public Relations Section of the Central Maluku Regent's Office. It was proved by the hypothesis test results, t count t table (12.989 2.068). Then the decision was to reject the hypothesis 0 (Ho) and accept the alternative hypothesis (Ha) meant there was a significant influence between Interperson Communication Against Employee Performance Enhancement in the Public Relations Office of the Central Maluku Regent Office. Keywords: Interpersonal Communication, Employee Performance